Gestational trophoblastic neoplasia: experience at Salah Azaiez Institute - Rim Batti; Amina Mokrani; Haifa Rachdi; Henda Raies; Omar Touhami; Mouna Ayadi; Khadija Meddeb; Feryel Letaief; Yosra Yahiaoui; Nesrine Chraiet; Amel Mezlini (The Pan African Medical Journal, 2019)

(untitled)
Gestational trophoblastic disease (GTD) develops from abnormal cellular proliferation of trophoblasts following fertilization. It includes benign trophoblastic disease (hydatidiform moles (HM)) and the malignant trophoblastic diseases or gestational trophoblastic neoplasia (GTN). The frequency of the GTD in Tunisia is one per 918 deliveries. The aim of this study is to analyze the clinical characteristics, treatment and outcomes of GTD at Salah Azaiez Institute (ISA). Medical records of women diagnosed with GTD at ISA from January 1st, 1981 to December 31st, 2012 were retrospectively reviewed. FIGO score was determined retrospectively for patients treated before 2002. One hundred and nine patients with GTN were included. Patients presented with metastases at 43% of cases. The most common metastatic sites was lung (30%) and vagina (13%). Fifty six (56 (51%) patients had low-risk and 21 (19%) cases had high-risk, the FIGO score was not assessed in 32 cases. After a median follow-up of 46 months, 21 patients were lost to follow-up, 12 patients died, 19 progressed and 8 relapsed. At 10 years, the OS rate was 85% and the PFS rate 79%. OS was significantly influenced by the presence of metastases at presentation (M0 100 % vs. Metastatic 62 %; p = 0.0001), FIGO stage (I-II 100% VS 61% and 65% for stage III and IV; p = 0.001), FIGO score (low-risk 99 % vs. high-risk 78 %; p =0.001). GTN is a significant source of maternal morbidity with increased risk of mortality from complications if not detected early and treated promptly.